ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH TERHADAP PEMBERITAAN MEDIA ONLINE PADA BERITA GEJOLAK PENGUNGSI ROHINGYA - Agus Dadang Hermawan; Agus Hamdani (Indonesian language and literature education program Majapahit Islamic University, 2023)
Critical Discourse Analysis (CDA) examines language as 'discourse,' where language is understood as one element within social processes that dialectically relate to each other. Critical discourse analysis precisely aims to explore these dialectical interconnections within the tradition of critical social science. In this research, the researcher will employ Norman Fairclough's model of critical discourse analysis, which examines discourse analysis through three theories: Text Analysis (Microstructural) related to cohesion and coherence, grammar, and diction; Production Practice Analysis (Mesostructural) dealing with the text production process, text dissemination, and text consumption, such as work patterns, workflow, and routines in news production; Social Cultural Practice Analysis (Macrostructural) related to situational, institutional, and social aspects. This study utilizes a qualitative descriptive method to deepen the critical analysis description of news discourse. The research data consists of words, phrases, or sentences in two online news discourses supporting the research problem. The data collection technique employed is documentary study. The news regarding the arrival of Rohingya refugees in Aceh published by VIVA.co.id becomes the focus of critical discourse analysis using Norman Fairclough's approach. This news reflects the text production process involving microstructural, mesostructural, and macrostructural aspects. In microstructural analysis, language use and representation are highlighted. Phrases like